Ethics for engineers a brief introduction - Bainbridge, Anthony F. (CRC Focus, 2022)
This book is a key introduction to ethics in engineering, providing professionals at all stages of their career with guidance on navigating the increasingly complex world of practising engineering ethically on an international scale.Engineering professionals face a duty to uphold reliable and trustworthy behaviour when working across all disciplines and industries. Accuracy and rigour are essential parts of the modern workplace, and are increasingly of concern to practising engineers. Using case studies to highlight examples of issues within the workplace and how these can be appropriately handled, this book is an accessible tool through which engineers can gain confidence in dealing with ethical dilemmas in the workplace. Touching upon safety, risk, artificial intelligence, autonomous systems, and intellectual property, alongside sustainability and environmental matters, the book focuses on hot topics which are fast becoming day-to-day issues dealt with by engineers.The book will be suitable for engineers of all disciplines, alongside students looking to become professional chartered engineers